2022
DOI: 10.1038/s41593-022-01095-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics and surface epitope detection in human brain epileptic lesions identifies pro-inflammatory signaling

Abstract: Epileptogenic triggers are multifactorial and not well understood. Here we aimed to address the hypothesis that inappropriate pro-inflammatory mechanisms contribute to the pathogenesis of refractory epilepsy (non-responsiveness to antiepileptic drugs) in human patients. We used single-cell cellular indexing of transcriptomes and epitopes by sequencing (CITE-seq) to reveal the immunotranscriptome of surgically resected epileptic lesion tissues. Our approach uncovered a pro-inflammatory microenvironment, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 47 publications
2
40
0
Order By: Relevance
“…DEGs for the merged clusters were calculated by Seurat's FindAllMarkers function. Each cluster was annotated by the top DEGs in reference to known marker of homeostatic macrophages and monocytes, as well as TREM2+ macrophages (which have been implicated in multiple human diseases such as cancer [35], obesity [36], atherosclerosis [118], and neurodegenerative diseases [119] (see Supplementary Table 1, Supplementary Table2) (Supplementary Figure 1-6D). We plotted the top 15 DEG with the highest fold change for each cluster in a heatmap in Supplementary Figure 1-6E, and highlighted the above-mentioned known markers.…”
Section: Integration and Clustering Of Monocytes/macrophages At The T...mentioning
confidence: 99%
See 1 more Smart Citation
“…DEGs for the merged clusters were calculated by Seurat's FindAllMarkers function. Each cluster was annotated by the top DEGs in reference to known marker of homeostatic macrophages and monocytes, as well as TREM2+ macrophages (which have been implicated in multiple human diseases such as cancer [35], obesity [36], atherosclerosis [118], and neurodegenerative diseases [119] (see Supplementary Table 1, Supplementary Table2) (Supplementary Figure 1-6D). We plotted the top 15 DEG with the highest fold change for each cluster in a heatmap in Supplementary Figure 1-6E, and highlighted the above-mentioned known markers.…”
Section: Integration and Clustering Of Monocytes/macrophages At The T...mentioning
confidence: 99%
“…To extract LAMs (from coronary atherosclerotic plaque), raw expression data from Wirka et al was processed following the authors' methods as closely as possible, using the parameters presided by the authors in the original publication [118]. DAM were defined as microglia clusters isolated from temporal lobe epilepsy patients provided by Kumar et al [119], and only temporal lobe microglia samples processed within the same batch were kept ('P6.A', 'P4', 'P5.A', P3.A'). The microglia were then scored for transcriptomic signature of DAM using Seurat's AddModuleScore function using default parameters (see Supplementary Table 2 for marker genes of this signature), and a z-score of DAM signature score was calculated.…”
Section: Comparison Of Spp1+mam+ Transcriptomic Signatures With Lams ...mentioning
confidence: 99%
“…Single-cell transcriptomics have identified cell-specific changes related to plasticity and inflammation, particularly in interneuron and glial populations ( Pfisterer et al, 2020 ; Kumar et al, 2022 ). Potential central regulators explaining glial genes expressed during epileptogenesis are directly upstream and regulate several MAPK pathways ( Kalozoumi et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, benzodiazepines and barbiturates, which are widely used antiepileptic drugs, exert their effect via enhancing GABA-mediated inhibition ( Treiman, 2001 ). More recently, it has been reported that neuroinflammation and neuronal apoptosis are also the main causes of epilepsy ( Henshall and Simon, 2005 ; Vezzani et al, 2019 ; Kumar et al, 2022 ).…”
Section: Overview Of Epilepsymentioning
confidence: 99%
“…Neuroinflammation is a contributing factor for many neuropsychiatric diseases including Alzheimer’s disease and depression ( Fang et al, 2020 ; Qi et al, 2021 ; Liu S. et al, 2022 ), and increasing evidence have demonstrated its role in the pathogenesis of epilepsy ( Vezzani et al, 2019 ; Kumar et al, 2022 ). Using single-cell cellular indexing of transcriptomes and epitopes by sequencing (CITE-seq) techniques, Kumar et al (2022) uncovered a pro-inflammatory microenvironment in the brain lesions of epileptic patients, including an extensive activation of microglia and an infiltration of other pro-inflammatory immune cells, together with a direct interaction between T cells and microglia. It is well known that activated microglia and astrocytes could interact with surrounding cells by secreting inflammatory factors, promoting neuroinflammatory responses into a vicious circle ( Ginhoux et al, 2010 ; Tian et al, 2012 ; Santiago et al, 2017 ; Fang et al, 2020 ; Liu S. et al, 2022 ).…”
Section: Role Of Long Non-coding Rnas In the Progress Of Epilepsy And...mentioning
confidence: 99%